2021
DOI: 10.2147/dddt.s319786
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Prediction and Molecular Docking-Based Strategy to Discover the Potential Pharmacological Mechanism of Huai Hua San Against Ulcerative Colitis

Abstract: Background: Huai Hua San (HHS), a famous Traditional Chinese Medicine (TCM) formula, has been widely applied in treating ulcerative colitis (UC). However, the interaction of bioactives from HHS with the targets involved in UC has not been elucidated yet. Aim: A network pharmacology-based approach combined with molecular docking and in vitro validation was performed to determine the bioactives, key targets, and potential pharmacological mechanism of HHS against UC. Materials and Methods: Bioactives and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 75 publications
(86 reference statements)
3
66
0
Order By: Relevance
“…Furthermore, QZZTD inhibited PI3K-AKt pathway activation, reduced inflammation, and alleviated UC. The aforementioned study also yielded the same results, revealing that TCM treatment of UC may mainly produce efficacy by regulating the PI3K-Akt signaling pathway ( Liu J. et al, 2021 ; Liu X. et al, 2021 ; Song et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, QZZTD inhibited PI3K-AKt pathway activation, reduced inflammation, and alleviated UC. The aforementioned study also yielded the same results, revealing that TCM treatment of UC may mainly produce efficacy by regulating the PI3K-Akt signaling pathway ( Liu J. et al, 2021 ; Liu X. et al, 2021 ; Song et al, 2021 ; Yu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, some studies have used network pharmacology combined with molecular docking to predict the efficacy and mechanism of drug action in UC, suggesting that potential mechanisms of drug action on the disease can be explored in this way. In a study composed of Huai Hua San formula, the investigators used this approach and validated it in vitro , discovering the binding properties of three key compounds (quercetin, luteolin, and nobiletin) to three key proteins (JUN, tumor protein P53, and estrogen receptor 1) and revealing the mechanism of quercetin affecting the protein expression of c-jun and the PI3K/Akt pathway to improve UC ( Liu J. et al, 2021 ). Another study also used this approach and combined it with animal studies to screen for key components (puerarin, baicalein, berberine, and glabridin) and key pathways (hypoxia inducible factor 1, PI3K-AKT, and TNF).…”
Section: Discussionmentioning
confidence: 99%
“…11 JUN, including JNK, JUNB and JUNC, belonged to the AP-1 transcription factor family and played an important role in the inflammatory response. 33 Y. Pan et al reported that the inhibition of JNK kinase activity could reduce the inflammatory response and apoptosis induced by high glucose, and protect the heart from the effects of diabetes. 34 These studies suggested that GPPGPA might regulate glucose consumption, cell activity and oxidative stress response of cells by acting on core targets such as AKT1, MAPK8, MAPK10 and JUN to improve insulin resistance and treat T2DM.…”
Section: Food and Function Papermentioning
confidence: 99%
“…[14][15][16] By network pharmacological analysis, Liu et al found 28 compounds and 421 targets in Huaihua-San formed the main pathways linked to ulcerative colitis, which revealed the mechanism of Huaihua-San against ulcerative colitis. 17 Similarly, with the help of network pharmacology, we predicted and verified the potential pharmacological mechanism of Bu-Yang herbs for postmenopausal osteoporosis via regulating the Wnt/β-catenin signaling pathway. 18 Therefore, all this evidence indicated that network pharmacology analysis may be a good tool for exploring the chemical compositions of LWDHD and its relationships with IVDD.…”
Section: Introductionmentioning
confidence: 90%